Level of Patients' Satisfaction with the Dental Care Provided at Private Dental Hospital, Peshawar - Yasir Khattak; Ruqayya Sana; Shakeel -; Ammara Sami; Gulandana Alam Khan; Michelle Khan (Gandhara University, 2017)
OBJECTIVE Quality is a major concern of health care authorities all over the world. Patient satisfaction regarding the dental treatment they receive is essential for the improvement of oral health service and practice. The aim of this study is to evaluate the levels of patient satisfaction regarding quality of dental care provided at Sardar Begum Dental Hospital. METHODS A random sampling technique based over one-month period; June 5th _ July 5th 2016 was used. Comprising of interviewer-administered questionnaires with a five point Likert scale (strongly agree, agree, uncertain, disagree, strongly disagree) to assess the level of patients' satisfaction with the dental services provided at the Sardar Begum Dental Hospital. RESULTS A total of 360 patients participated that has received and/or was still receiving treatment at Sardar Begum Dental Hospital with a response rate of 73 %.The overall estimate of factors related to satisfaction showed a mean percentage of74.8% for the 4 disciplines of satisfaction displaying a high level of satisfaction. CONCLUSION Majority of patients receiving treatment at Sardar Begum Dental Hospital were satisfied with dentist-patient interaction, administrative efficiency, technical competency and hospital environment.